2021
DOI: 10.1007/s11104-021-04922-z
|View full text |Cite
|
Sign up to set email alerts
|

EDXRF for screening micronutrients in lentil and sorghum biofortification breeding programs

Abstract: Background and aims This study explores the use of energy dispersive x-ray fluorescence (EDXRF) for screening micronutrient concentrations in lentil and sorghum grain for biofortification breeding programs. Methods Lentil and sorghum seed was provided from biofortification breeding programs and analysed with inductively coupled plasma mass spectrometry (ICP-MS) to determine the reference concentration levels of Ca, Mn, Fe, Cu and Zn. A subset of these samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…However, the requirement for samples being ground, pressed and analysed under a vacuum increases both the time and cost of analysis. It has previously been shown that Ca analysis of whole seeds under an air atmosphere is feasible (Guild and Stangoulis 2021). These results show it is possible to analyse the smaller seed crops (rice and pearl millet) as whole grain and still produce a robust calibration and validation (r 2 > 0.9), however the remaining crops required seed to be ground to flour to produce suitably robust calibrations as seen in Figure 1.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…However, the requirement for samples being ground, pressed and analysed under a vacuum increases both the time and cost of analysis. It has previously been shown that Ca analysis of whole seeds under an air atmosphere is feasible (Guild and Stangoulis 2021). These results show it is possible to analyse the smaller seed crops (rice and pearl millet) as whole grain and still produce a robust calibration and validation (r 2 > 0.9), however the remaining crops required seed to be ground to flour to produce suitably robust calibrations as seen in Figure 1.…”
Section: Discussionmentioning
confidence: 80%
“…EDXRF requires minimal sample preparation and a fast non-destructive analysis requiring minimal consumables and a rapid analysis time. EDXRF analysis of Ca in various food products has been reported previously (Perring and Andrey 2003;Perring and Andrey 2018;Perring et al 2019) in plants and food crops (Ekinci et al 2004;Guild and Stangoulis 2021;Kalcsits 2016). To develop a robust XRF calibration it is essential to have samples with robust reference values and a wide range of concentrations for the element(s) of interest.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations